A Brand Culture Approach to Managing Nation‐Brands. Issue 1 (24th September 2017) - Yalkin, Cagri
Abstract : The objective of this note is to formulate conceptual links between nation brands, international relations, and politics through the development of research questions that are underpinned by a brand‐culture approach. The focus is on the export of Turkey's soap operas to diverse locations around the globe, but in particular to the Middle East and the Balkans. The note calls for: (1) forging a dialogue across international relations, political science, media, and management studies through a brand‐culture lens which allows for a historical understanding; (2) focusing on historical and political discourses as resources in interpreting nation brands and cultural and creative goods; and, (3) focusing on nation branding between countries in the Global South. Forging a dialogue across disciplines and focusing on how consumers make use of historical and political discourses informs both commercial and diplomatic co‐creators of nation brands.